Continuous Exposure of Breast Cancer Cells to Tamoxifen Upregulates GPER-1 and Increases Cell Proliferation - Molina, Luis; Bustamante, Felipe; Ortloff, Alexander; Ramos, Iraidi; Ehrenfeld, Pamela; Figueroa, Carlos D. (Frontiers in Endocrinology, 2020)
GPER-1 is a novel membrane sited G protein-coupled estrogen receptor. Clinical studies have shown that patients suffering an estrogen receptor α (ERα)/GPER-1 positive, breast cancer have a lower survival rate than those who have developed ERα-positive/GPER-1 negative tumors. Moreover, absence of GPER-1 improves the prognosis of patients treated with tamoxifen, the most used selective estrogen receptor modulator to treat ERα-positive breast cancer. MCF-7 breast cancer cells were chronically treated with 1000 nM tamoxifen to investigate its effect on GPER-1 protein expression, cell proliferation and intracellular [Ca2+]i mobilization, a key signaling pathway. Breast cancer cells chronically treated with tamoxifen, for seven days, exhibited a robust [Ca2+]i mobilization after stimulation with 1000 nM tamoxifen, a response that was blunted by preincubation of cells with G15, a commercial GPER-1 antagonist. Chronically treated cells also displayed a high [Ca2+]i mobilization in response to a commercial GPER-1 agonist (G1) and to estrogen, in a magnitude that doubled the response observed in untreated cells and was almost completely abolished by G15. Proliferation of cells chronically treated with tamoxifen and stimulated with 2000 nM tamoxifen, was also higher than that observed in untreated cells in a degree that was approximately 90% attributable to GPER-1. Finally, chronic tamoxifen treatment did not increase ER expression, but did overexpress the kinin B1 receptor, another GPCR, which mediates the proliferative response of breast cancer cells, Our results shed some light on the occurrence of drug resistance in breast cancer patients who are ERα/GPER-1 positive, have been treated with tamoxifen and display low survival rate. Overexpression of kinin B1 receptor may explain the increased proliferative response observed in breast tumors under chronic treatment with tamoxifen.